The transcriptional repressor Sum1p counteracts Sir2p in regulation of the actin cytoskeleton, mitochondrial quality control and replicative lifespan in Saccharomyces cerevisiae - Ryo Higuchi-Sanabria; Jason D. Vevea; Joseph K. Charalel; Maria L. Sapar; Liza A. Pon (Microbial Cell)
Increasing the stability or dynamics of the actin cytoskeleton can extend lifespan in C. elegans and S. cerevisiae. Actin cables of budding yeast, bundles of actin filaments that mediate cargo transport, affect lifespan control through effects on mitochondrial quality control. Sir2p, the founding member of the Sirtuin family of lifespan regulators, also affects actin cable dynamics, assembly, and function in mitochondrial quality control. Here, we obtained evidence for novel interactions between Sir2p and Sum1p, a transcriptional repressor that was originally identified through mutations that genetically suppress sir2∆ phenotypes unrelated to lifespan. We find that deletion of SUM1 in wild-type cells results in increased mitochondrial function and actin cable abundance. Furthermore, deletion of SUM1 suppresses defects in actin cables and mitochondria of sir2∆ yeast, and extends the replicative lifespan and cellular health span of sir2∆ cells. Thus, Sum1p suppresses Sir2p function in control of specific aging determinants and lifespan in budding yeast.